2016
DOI: 10.3847/0004-637x/832/1/24
|View full text |Cite
|
Sign up to set email alerts
|

PHOTO-STABILITY OF SUPER-HYDROGENATED PAHs DETERMINED BY ACTION SPECTROSCOPY EXPERIMENTS

Abstract: We have investigated the photo-stability of pristine and super-hydrogenated pyrene cations (C 16 H + 10+m , m = 0, 6, or 16) by means of gas-phase action spectroscopy. Optical absorption spectra and photo-induced dissociation mass spectra are presented. By measuring the yield of mass-selected photo-fragment ions as a function of laser pulse intensity, the number of photons (and hence the energy) needed for fragmentation of the carbon backbone was determined. Backbone fragmentation of pristine pyrene ions (C 16… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…These studies showed that it is possible to superhydrogenate PAH cations, with a clear preference for the addition of an odd number of H atoms, suggesting that PAH cations could act as a catalyst for H 2 formation. Hydrogenation of PAH cations has been suggested to protect PAHs from photoinduced fragmentation (Reitsma et al 2014), while other studies suggest that the weakening of the carbon skeleton as a result of H atom addition might actually lead to hydrogenated PAHs being more prone to fragmentation (Gatchell et al 2015;Wolf et al 2016). Sequential hydrogenation has also been demonstrated to lead to fragmentation as a result of the exothermic C-H bond formation process, although the low H-atom fluxes present in the ISM make this an unlikely scenario (Rapacioli et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that it is possible to superhydrogenate PAH cations, with a clear preference for the addition of an odd number of H atoms, suggesting that PAH cations could act as a catalyst for H 2 formation. Hydrogenation of PAH cations has been suggested to protect PAHs from photoinduced fragmentation (Reitsma et al 2014), while other studies suggest that the weakening of the carbon skeleton as a result of H atom addition might actually lead to hydrogenated PAHs being more prone to fragmentation (Gatchell et al 2015;Wolf et al 2016). Sequential hydrogenation has also been demonstrated to lead to fragmentation as a result of the exothermic C-H bond formation process, although the low H-atom fluxes present in the ISM make this an unlikely scenario (Rapacioli et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Wolf et al (2016) shows that the so-called super-hydrogenated polycyclic aromatic hydrocarbons 10 , which could be considered as analogues of a-C(:H) nano-particles, are less stable against photodissociation than their fully aromatic equivalents. Thus, and in the absence of laboratory data and models for a-C(:H) nanoparticle excitation and photo-dissociative processing, the work of Micelotta et al (2010bMicelotta et al ( ,a, 2011, which applies to fullerene and polycyclic aromatic hydrocarbons, can only be used to give an upper limit to the lifetime of a-C(:H) nano-grains with the same number of carbon atoms as fully aromatic particles.…”
Section: Dust Processing In High Energy Environmentsmentioning
confidence: 99%
“…This approach led us to a self-consistent explanation for the origin of the UV extinction bump in a-C nano-particles (a 1 nm, Jones 2012c) and also to viable routes to interstellar/circumstellar fullerene formation through UV 10 N.B. Small super-hydrogenated polycyclic aromatic hydrocarbons with less than 20 C atoms (e.g., Wolf et al 2016) cannot be aromatic and should therefore strictly be called polycyclic aliphatic hydrocarbons.…”
Section: Dust Processing In High Energy Environmentsmentioning
confidence: 99%
“…Experimentally, it has been demonstrated that coronene (C 24 H 12 ) could be fully superhydrogenated to form perhydrocoronene (C 24 H 36 ) in low UV flux regions (see Thrower et al 2012Thrower et al , 2014. Wolf et al (2016) explored experimentally the photo-stability of cationic pyrene (C 16 H 10 + ) with six (C 16 H 16 + ) or 16 extra H atoms (C 16 H 26 + ) and found superhydrogenated pryene cations would undergo backbone fragmentation upon absorption of two (for C 16 H 16 + ) or one (for C 16 H 26 + ) photons of energy just below 3 eV. On the other hand, by combining thermal desorption mass spectrometry measurements and density functional theory (DFT) calculations, Jensen et al (2019) have shown the existence of stable configurations of superhydrogenated neutral coronene.…”
Section: Introductionmentioning
confidence: 99%